Dynamics of an inverted cantilever plate at moderate angle of attack. (29th December 2020) - Huertas-Cerdeira, Cecilia; Goza, Andres; Sader, John E.; Colonius, Tim; Gharib, Morteza
Abstract: Abstract : The dynamics of a cantilever plate clamped at its trailing edge and placed at a moderate angle ( α ≤ 30^° ) to a uniform flow are investigated experimentally and numerically, and a large experimental data set is provided. The dynamics are shown to differ significantly from the zero-angle-of-attack case, commonly called the inverted-flag configuration. Four distinct dynamical regimes arise at non-zero angles: a small oscillation around a small-deflection equilibrium (deformed regime), a small-amplitude flapping motion, a large-amplitude flapping motion and a small oscillation around a large-deflection equilibrium (deflected regime). The small- and large-amplitude flapping motions are shown to be produced by different physical mechanisms. The small-amplitude flapping motion appears gradually as the flow speed is increased and is consistent with a limit-cycle oscillation caused by the quasi-steady fluid forcing. The large-amplitude flapping motion is observed to appear at a constant critical flow speed that is independent of angle of attack. Its characteristics match those of the large-amplitude vortex-induced vibration present at zero angle of attack. The flow speed at which the plate enters the deflected regime decreases linearly as the angle of attack is increased, causing the flapping motion to disappear for angles of attack greater than α ≈ 28^° . Finally, the effect of aspect ratio on the plate dynamics is considered, with a plate of reduced aspect ratio being shown to lack a sharp distinction between flapping regimes for α >8^° .